IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI EKSTRAKURIKULER SENI TARI DI SD NEGERI 12 PADANG LUA KECAMATAN BANUHAMPU KABUPATEN AGAM - Yelfianita; Farida Mayar; Desyandri (STKIP Subang, 2023)
This study aims to describe the implementation of character education through extracurricular dance activities at Padang Lua Banuhampu subdistrict Agam regency 12 state elementary school. This research is a qualitative descriptive study. The data source of the study consisted of principals, dance teachers, class III-V teachers,and students of class III-V. The technique of collecting data is done by interviews, observation, and documentation.Check data validity using source, technique, and time triangulation. The data analysis technique used is the Milles and Huberman model where researchers conduct data collection, data reduction, data presentation, and conclusion drawing.